Prevalence of vulvovaginitis and relation to physical findings in girls assessed for suspected child sexual abuse - Rahman, Gisel (2015)
Introduction. The presence of sexually transmitted infections (STIs) in patients with suspected sexual abuse is uncommon in the field of pediatrics. Objectives. To establish the prevalence of anogenital findings and their relation to the presence of STIs in girls referred for suspected child sexual abuse. Material and Methods. Retrospective study conducted between January 1st, 2003 and December 31st, 2013. Physical findings and detection of STIs in girls with suspected child sexual abuse were analyzed. Results. One thousand thirty-four patients were included. Their median age was 7.9 years old. Anogenital findings were classified as class I (normal): 38.4%, class II (nonspecific): 38.1%, class III (specific): 19.9% and class IV (definitive): 3.6%. STIs were observed in 42 patients (4.1%). A relation was established between STIs and the classification of physical findings: 10 (class II: 9; class III: 1) Neisseria gonorrhoeae, 17 (class I: 2; class II: 8; class III: 7) Chlamydia trachomatis, 15 (class I: 2; class II: 10; class III: 3) Trichomonas vaginalis. Statistically significant differences for Trichomonas vaginalis (p= 0.01) and Neisseria gonorrhoeae (p < 0.0001) were observed, with predominance of nonspecific clinical signs. Both nonspecific and specific findings were similarly observed for Chlamydia trachomatis (p= 0.03). Conclusions. Most cases of girls with suspected child sexual abuse had normal or nonspecific anogenital findings. The prevalence of STIs in these girls is low. Trichomonas vaginalis and Neisseria gonorrhoeae were related to nonspecific findings, while both nonspecific and specific findings were observed for Chlamydia trachomatis.